A Surface Acoustic Wave Ethanol Sensor with Zinc Oxide Nanorods. (26th December 2011) - Giffney, Timothy J.; Ng, Y. H.; Aw, K. C.
Abstract : Surface acoustic wave (SAW) sensors are a class of piezoelectric MEMS sensors which can achieve high sensitivity and excellent robustness. A surface acoustic wave ethanol sensor using ZnO nanorods has been developed and tested. Vertically oriented ZnO nanorods were produced on a ZnO/128 ∘ rotated Y-cut LiNbO3 layered SAW device using a solution growth method with zinc nitrate, hexamethylenetriamine, and polyethyleneimine. The nanorods have average diameter of 45 nm and height of 1  μ m. The SAW device has a wavelength of 60 um and a center frequency of 66 MHz at room temperature. In testing at an operating temperature of 270C ∘ with an ethanol concentration of 2300 ppm, the sensor exhibited a 24 KHz frequency shift. This represents a significant improvement in comparison to an otherwise identical sensor using a ZnO thin film without nanorods, which had a frequency shift of 9 KHz.